Financing Lifelong Learning - Oosterbeek, Hessel (The World Bank, 2008)
This paper describes and analyzes different financial schemes to promote lifelong learning. Considered are financial instruments to stimulate successful early learning, financial aid schemes and subsidization mechanisms. Theoretical analyses about funding of early learning have mainly focused on vouchers. Yet, the available empirical evidence is more ambiguous about the effects of vouchers than about the effects of conditional cash transfers and financial incentives for pupils and teachers. Positive effects of financial incentives to pupils are not restricted to high ability pupils, as low ability students also seem to benefit. The evidence regarding the effects of subsidy forms is limited. The most prominent knowledge gaps regarding the effects of various financing schemes related to lifelong learning are the effects of vouchers in compulsory education; financial aid schemes for students; and entitlements and individual learning accounts